2008
DOI: 10.1002/ppul.20767
|View full text |Cite
|
Sign up to set email alerts
|

Review of optimal characteristics of face‐masks for valved‐holding chambers (VHCs)

Abstract: Inhaled drugs are frequently given to infants and young children with a pressurized metered-dose inhaler (pMDI) attached to a valved-holding chamber (VHC) with face mask. In young children and infants who cannot breathe through a mouthpiece, the face mask serves as the interface between the patient and the VHC. Although the mask interface is one of the most important factors determining the dose of medication delivered from the VHC to the nose and mouth in these patients, its optimal characteristics are not we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
0
35
0
1
Order By: Relevance
“…Achieving a good facemask-to-face seal is therefore critical, and depends in part on the design of the facemask. (8) Although a number of VHC-facemask combinations are commercially available, current research has focused on the development of new facemasks, intended to improve inhalation therapy in young children. In vitro testing is an important part of the facemask development process, prior to in vivo application.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving a good facemask-to-face seal is therefore critical, and depends in part on the design of the facemask. (8) Although a number of VHC-facemask combinations are commercially available, current research has focused on the development of new facemasks, intended to improve inhalation therapy in young children. In vitro testing is an important part of the facemask development process, prior to in vivo application.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies emphasized the importance of a good face mask seal and reported that the face mask was not tolerated by children during aerosol therapy. (12)(13)(14)(15)(16)(17)(18)(19)(20) Also, the practice of blow-by, directing the stream of aerosol to the face of a child has been associated with reduced delivery compared to a tightly fitting mask, with variable deposition associated with nebulizer type. (21) Although nebulizers are well-established devices in aerosol medicine, there are different types of nebulizers and interfaces used for aerosol therapy that raise some practical questions among clinicians in the treatment of adults and pediatrics with pulmonary diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The seal between the mask and the infant's face also depends on face-mask design. 18 More than 10 years ago, Everard et al 19 showed that with a small-volume jet nebulizer, even a 1-cm gap between the mask and the face reduced the dose delivered to the respiratory tract by 50%. A good seal has been repeatedly shown to be required for efficient aerosol delivery to the LRT.…”
Section: Face-mask Seal and Designmentioning
confidence: 98%
“…A good seal has been repeatedly shown to be required for efficient aerosol delivery to the LRT. 17,18 Drug delivery can be improved by use of a round face mask with a flexible rim. 18 Sangwan et al 20 correctly called attention to different effects of design on nebulizers compared with VHCs.…”
Section: Face-mask Seal and Designmentioning
confidence: 99%
See 1 more Smart Citation